BIOACTIVE COMPOUNDS IN ETHANOL EXTRACT OF LENTINUS SQUARROSULUS MONT - A NIGERIAN MEDICINAL MACROFUNGUS - Adeoye-Isijola, Morenike Olutunmbi; Olajuyigbe, Olufunmiso Olusola; Jonathan, Segun Gbolagade; Coopoosamy, Roger Murugas (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: The continuous search for new lead compounds of therapeutic importance has become necessary in the face of treatment failures and multidrug resistance plaguing the world. While many plants and higher fungi are sources of bioactive compounds yet to be fully harnessed, understanding the bioactive components in macrofungus could serve as a lead for investigating its biological activities and medicinal potentials. Materials and Methods: The bioactive compounds in the ethanolic extract of Lentinus Squarrosulus, an edible Nigerian macrofungus, were investigated by Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Results: There were nine bioactive compounds in this edible macrofungus. Of these compounds, 9,12-Octadecanoic acid ethyl ester (37.39%; RT:39.815) was the highest in quantity, followed by Hexadecanoic acid ethyl ester (14.49%; RT:36.550). Other fatty acids, their ethyl esters and other compounds identified included 2-Butenethioic acid,3-(ethylthio)-S-(1-methylethyl) ester (4.51%; RT:15.866), n-Hexadecanoic acid (4.74%; RT:36.034), 9,12-Octadecadienoic acid (Z,Z)- (11.88%; RT:39.429), 9,17-Octadecadienal,(Z)- (5.01%; RT:39.500), ethyl oleate (5.27%; RT:39.898), 3a,6-Methano-3aH-indene,2,3,6,7 tetrahydro (4.04%; RT:48.379), and 9,12-Octadecadienoic acid (Z,Z)-,2 hydroxy-1-(hydroxymethyl) ethyl ester (12.68%; RT:48.682). Some of these compounds have antimicrobial, antioxidant, hepatoprotective, hypocholesterolemic as well as cancer preventive activities amongst others. Conclusion: This study showed the bioactive components of therapeutic potentials in L. squarrosulus while creating a platform for screening, isolating and identifying many bioactive components which may be useful in the treatment of the various ailments, disorders and diseases in the nearest future.